Phonological Awareness On Preschool Students’ Writing Ability - Aruan, Erna Juliana (Pascasarjana Universitas HKBP Nommensen, 2023)
Phonological awareness is the area of oral language that relates to the ability to think about thesounds in a word. It is an understanding of the structure of spoken language that it is made up ofwords consist of syllables, rhymes and sounds. This ability is important for using sound-letterknowledge effectively in writing and reading as well. This research conducted the assessment ofpreschool students ability in writing the dictated words through their phonological awareness not bymemorizing the letters. There were 19 students assessed in this research. 2 out of 19 were failed toimprove in the vowel sound of oo and oa. 17 out of 19 were success to be improving after givingphonological awareness.